Mandy's 8 theories of sleep - Li, Minghui (2010)
The script was co-written by the director and the writer/production designer. The dialogues of the characters were originally written in English, however, the director wanted the story to be in Mandarin, which meant the dialogues had to be translated into Mandarin. The task of translating the dialogues was given to me. The original dialogues were mysterious and surreal, using the rich and surreal vocabulary. However, to translate the English dialogues to Mandarin dialogues proved to be a tedious task as both languages differ widely. On top of that, the dialogues were spoken by primary school kids which meant that the Chinese used should be of a child’s level, and too high of an adult. Furthermore, in this modern Singapore young generation, majority of the children no longer speaks pure Mandarin. They speak with a mix of languages: Mandarin, English and other dialects.